A review on ionic liquids as perspective catalysts in transesterification of different feedstock oil into biodiesel - Ullah, Z. (Elsevier B.V., 2018)
The past few decades had seen a rapid hike in the world's population, which has caused an excessive use of fossils and, consequently, the diminution of fossil resources and the advent of global pollution problems. In this regard, the renewable and eco-friendly properties of biodiesel fuel provide an alternative to petroleum fuel. Many countries are looking into the use of biodiesel, particularly countries that are more susceptible to environmental problems. Biodiesel could be synthesized from different origins, including organic oils from animal fats and vegetables. At the same time, the production of biodiesel from vegetable edible oils can create food security problems; hence, the selection of cheap sources, like animal fats, is a valuable feedstock, but its availability is limited. Thus, more preferable sources other than low-cost feedstocks with high free fatty acids content include unrefined crude oils, discarded cooking oil and inedible oils. This paper is aimed to highlight biodiesel and its availability from various feedstock for its preparation. It also discussed how the ionic liquids (ILs) can be the catalysts to produce biodiesel; these liquids are sourced by different feedstocks by transesterification method. Due to several limitations and problems associated with traditional homogeneous and heterogeneous catalysts in recent years, ILs are increasingly used as the catalysts or solvents for free fatty acids esterification, as well as the transesterification of vegetable oils. This paper is focused on the transesterification of fatty acid with ILs, cost and recycling of ILs, the effects of adding enzyme, Lewis acids and amines on ILs catalysed reaction, the use of BrÃ¸nsted acidic, basic and dicationic basic ILs as the sole solvent which supported acid/base-catalysed IL for biodiesel synthesis. In addition, the proper research focuses and new developments in this regard would make the ILs as an ideal catalyst for biodiesel preparation from various feedstocks. Â© 2018 Elsevier B.V.